Sport(scape) : gateway to the Ellis Park sports precinct - accessibility and inclusion through education and health - Newell, Kim (My University, 2014)
South Africa has a history of segregation and prejudice. In the past sport has been used as an oppressive force to control certain population groups. Even today, 19 years after democracy was established, not everybody has equal access to sporting facilities. This project centres around the Ellis Park Sports Precinct and investigates how the facilities found in the precinct can be made more accessible to a broader range of users, at both a local and regional level. The majority precinct is currently used by elite sportsmen with only certain facilities available for general use. The precinct has good links to education, healthcare and community facilities and through this paper these links will be explored and incorporated in the design intervention. This valuable precinct is under-utilised and goes for long periods of time with very little activity. It is only during major sporting events, at certain times of the year, that the precinct comes to life. The precinct contains vast amounts of open space and is surrounded by high density residential areas. This space has the potential to be visited throughout the year through an intervention that uses sport to create a link between health, community and education. The design intervention uses sport to create a link between the Ellis Park Precinct and the surrounding community as well as the nearby educational institutions.